Three‐Dimensional Electrical Conductivity and Induced Polarization Tomography of a Rock Glacier. Issue 11 (22nd November 2018) - Duvillard, P. A.; Revil, A.; Qi, Y.; Soueid Ahmed, A.; Coperey, A.; Ravanel, L.
Abstract: Three‐dimensional electrical resistivity and induced polarization data were collected on an unstable Alpine rock glacier in Val Thorens (Vanoise massif, France). In addition to these field data, we also performed induced polarization measurements during freeze and thaw using a soil sample and the poorly mineralized water, both from this site. In the tomograms, the electrical conductivity and the normalized chargeability show very distinctly the presence of the rock ice mixture. The chargeability itself is however quite constant over the entire investigated area with the exception of a small area associated with the presence of carboniferous rocks rich in graphite. The background chargeability is close to the dimensionless number R  = 8 × 10 −2, which is consistent with the prediction of the dynamic Stern layer model for the polarization of porous media. The theory implies that this dimensionless number R is independent on saturation and temperature in agreement with field observations. A main implication of this observation is that the classical Archie's law cannot be applied to describe the electrical conductivity in this type of environments with poorly mineralized pore water. Surface conductivity dominates the measured conductivity of the materials implying in turn that the electrical conductivity is related to both the water content and cation exchange capacity of the material. We propose new equations for both the electric conductivity and the normalized chargeability in this type of environments. Plain Language Summary: Induced polarization is a geophysical method looking at imaging the 3D distribution of properties related to the ability of rocks to store reversibly electrical charges under the application of a primary electrical field. This method has never been applied to rock glaciers. A field application and a laboratory experiment demonstrate the usefulness of this method to characterize Alpine rock glaciers and point up some shortcomings in the interpretation of electrical conductivity tomography done by previous authors in this type of environments. Key Points: Induced polarization of rock glacier is investigated. During freeze and thaw, rocks show two polarization effects Surface conductivity controls the rock electrical conductivity of rocks during freeze and thaw An experiment and a field study on an Alpine rock glacier are performed to investigate the electrical conduction in freezing conditions